CFD simulation of sugarcane bagasse combustion in an industrial grate boiler (2018)
The simulation of an industrial boiler in CFD (Computational Fluid Dynamics) is usually done by stages due to the extensive size and the different physical phenomena that occur in different locations of the equipment. In this work, the simulation of an industrial grate boiler is done in three stages, one for the primary air circuit, another one for the secondary air circuit and the final one is the furnace. The combustion of sugarcane bagasse is a complex phenomenon that involves moisture vaporization, devolatilization and char combustion, in order to account for those phenomena, bagasse particles were modeled in a Eulerian-Lagrangian approach. The simulations were performed in commercial software ANSYS FLUENT and the devolatilization model were programmed in C language as a User Defined Function (UDF). When the results of the simulations were compared with experimental data, a satisfactory agreement was observed. Simulations were performed with primary and secondary air inlets modifications in order to optimize the boiler performance, the results of those simulations showed significant improvement in the combustion parameters.